APLIKASI METODE ELEKTROKOAGULASI TERHADAP PENURUNAN KADAR ION LOGAM Fe DAN Mn, KEKERUHAN SERTA WARNA PADA PENGOLAHAN AIR GAMBUT SECARA BATCH - Kurniasih, Ririn Feby; Gunawan, Rahmat; Panggabean, Aman Sentosa (Jurusan Kimia FMIPA UNMUL, 2016)
The research about application of electrocoagulation method regarding the decrease level of metal ion such Fe, Mn, turbidity and color on peat water treatment ini batch method had been done. The research in batch method using alumunium (Al) plat as electrode until obtained higher efficiency elimination on voltages of 12 volt with electrocoagulation process time, 120 minute in batch method. The result on variation of voltages was capable to decrease Fe level with efficiency 99.87% from 3.6899 mg/L become 0.0045 mg/L and followed by Mn 95.90% from 0.0244 mg/L become -0.0008 mg/L, turbidity 98% from 385 NTU become 0,95 NTU and color 97.67% from 338.08 Pt-Co become 7.8646 Pt-Co. Long term variation of contact was capable to decrease fe level with efficiency 99.57% from 3.6899 mg/L to 0.0158 mg/L followed by Mn 93.03% from 0.0244 mg/L become 0.0017 mg/L, turbidity 99.74% from 385 NTU to 0.97 NTU and color 98.73% from 338.08 Pt-Co become 4.2985 Pt-Co. Elimination percent has proving electrocoagulation method was capable to decreasing the level of Fe ion, Mn, turbidity and color on peat water and comply the regulation of healthy minister Indonesia Republic No 416/MENKES/PER/IX/1990 regarding clean water quality Keywords :Peat Water, Electrocoagulation, Fe, Mn, Turbidity, Color Intensity